Curcumin Activates AMPK Pathway and Regulates Lipid Metabolism in Rats Following Prolonged Clozapine Exposure - Liu, Zhen; Cui, Changmeng; Xu, Pengfei; Dang, Ruili; Cai, Hualin; Liao, Dehua; Yang, Mengqi; Feng, Qingyan; Yan, Xin; Jiang, Pei (Frontiers in Neuroscience, 2017)
Clozapine (CLO) remains an ultimate option for patients with treatment resistant schizophrenia. However, the atypical antipsychotic is often associated with serious metabolic side effects, such as dyslipidemia. Hepatic sterol regulatory element-binding proteins (SREBPs) are central in the allosteric control of a variety of lipid biosynthetic pathways. There is emerging evidence that CLO can activate SREBP pathway and enhance downstream lipogenesis, whereas curcumin (CUR), a major active compound of Curcuma longa, contains hypolipidemic properties. Therefore, in the present study, we examined the protective effects of CUR against CLO-induced lipid disturbance and analyzed the expression of key components in hepatic lipid metabolism. Our data showed that 4-week treatment of CLO (15 mg/kg/day) markedly elevated serum lipid levels and resulted in hepatic lipid accumulation, whereas co-treatment of CUR (80 mg/kg/day) alleviated the CLO-induced dyslipidemia. We further demonstrated that CUR appears to be a novel AMP-activated protein kinase (AMPK) agonist, which enhanced AMPK phosphorylation and mitigated CLO-induced SREBP overexpression. Additionally, CUR also modulated the downstream SREBP-targeted genes involved in fatty acid synthesis and cholesterol metabolism, including fatty acid synthase (FAS) and HMG-CoA reductase (HMGCR). In summary, our study suggests that the suppressed AMPK activity and thereby enhanced SREBP-dependent lipid synthesis could be associated with the antipsychotic-stimulated dyslipidemia, whereas CUR may maintain lipid homeostasis by directly binding to AMPK, indicating that adjunctive use of CUR could be a promising preventive strategy for the drug-induced lipogenesis.